2023
DOI: 10.1021/acs.cgd.2c01444
|View full text |Cite
|
Sign up to set email alerts
|

Stacks of Equidistant 5,6-Dichloro-2,3-dicyanosemiquinone (DDQ) Radicals under Variable-Temperature and High-Pressure Conditions

Abstract: The effects of temperature (80−400 K) and pressure (up to 4.67 GPa) variations on stacks of equidistant semiquinone radicals were studied by single-crystal X-ray diffraction using a salt of 2-amino-5-methyl-N-methylpyridinium (MMA) and 5,6-dichloro-2,3-dicyanosemiquinone radical anion (DDQ). A temperature-driven phase transformation occurs in the temperature range 150−240 K. The nature of stacking changes upon cooling: equidistant radicals in the room-temperature phase are re-arranged into two-electron/multice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Racioppi et al, 2020;Sorbara et al, 2022;Montisci et al, 2023: Stachowicz et al, 2023, structure-property correlation (e.g. Tchon ´et al, 2021;Gajda et al, 2020Gajda et al, , 2023Milas ˇinovic ´et al, 2021;Molc ˇanov et al, 2019;Stanic ´et al, 2023;Patten et al, 2023), QSAR (e.g. Vigneau et al, 2022), etc.…”
Section: Properties From Refined Charge Densities and Wavefunctionsmentioning
confidence: 99%
“…Racioppi et al, 2020;Sorbara et al, 2022;Montisci et al, 2023: Stachowicz et al, 2023, structure-property correlation (e.g. Tchon ´et al, 2021;Gajda et al, 2020Gajda et al, , 2023Milas ˇinovic ´et al, 2021;Molc ˇanov et al, 2019;Stanic ´et al, 2023;Patten et al, 2023), QSAR (e.g. Vigneau et al, 2022), etc.…”
Section: Properties From Refined Charge Densities and Wavefunctionsmentioning
confidence: 99%
“…For compounds with stacking interactions, the distances between the rings may be at least equally important for the anisotropy of structural response to temperature and pressure variations (Resnati et al, 2015;Bogdanov et al, 2020;Milas ˇinovic ´et al, 2021;Stanic ´et al, 2023). We have analysed the effects of increasing pressure and cooling on the two types of distances between guaninate planes in K + ÁC 5 H 4 N 5 O À ÁH 2 O, and in 2Na + ÁC 5 H 3 N 5 O 2À Á7H 2 O.…”
Section: Changes In Hydrogen Bonds Under Compressionmentioning
confidence: 99%
“…A full list of structures with CSD ref codes are given in Table S7. While the low number of structures and different temperatures of data collection (varying from 90 to 293 K; it has been shown that the length of pancake bonding is temperature-dependent , ) preclude statistical analysis of geometry, some conclusions can be drawn, nevertheless. The closest distance between two C atoms, proposed by Miller and Novoa et al .…”
Section: Introductionmentioning
confidence: 99%